A goal programming approach to multi-objective optimization of firefighting strategies in the event of domino effects - Khakzad, Nima (Reliability engineering & system safety, 2023)
•Optimal firefighting strategies are identified via goal programming.•Objectives include minimizing onsite and offsite risks arising from domino effects.•Land use planning is used to determine offsite risk thresholds.•Bayesian network is used to derive probabilities of potential domino effect. In the event of fire in tank terminals, an ideal firefighting strategy would include simultaneous suppression of all burning tanks and cooling of all exposed tanks. This strategy, if effective, would confine the fire and prevent its escalation throughout the plant. However, limited firefighting resources, which is the case at most tank terminals, do not usually allow for conducting an ideal firefighting particularly if fire propagates from an originally burning tank to adjacent tanks, creating a domino effect. As such, an optimal strategy would be needed to determine which burning tanks to suppress and which exposed tanks to cool so as to best satisfy the safety objectives. For tank terminals that are near communities or offsite assets, the situation can become more challenging as a multi-objective firefighting strategy would be needed not only to limit the possibility and extent of domino effects within the plant but also to protect people and assets located outside the premises of the plant. For this purpose, in the present study, a methodology is developed based on goal programming – a multi-objective optimization technique – for identifying optimal firefighting strategies while considering both onsite and offsite risks of domino effects. The resulting firefighting strategies are demonstrated to be more effective and consistent than the ones identified using single-objective optimization techniques or general guidelines.